The effect of different dietary levels of hybrid rye and xylanase addition on the performance and egg quality in laying hens. Issue 4 (4th July 2019) - Bederska-Łojewska, D.; Arczewska-Włosek, A.; Świątkiewicz, S.; Orczewska-Dudek, S.; Schwarz, T.; Puchała, M.; Krawczyk, J.; Boros, D.; Fraś, A.; Micek, P.; Rajtar, P.
ABSTRACT: 1. In this study, 240 ISA Brown hens were fed diets containing different levels of hybrid rye, and the influence of xylanase addition on laying performance and egg quality was evaluated. 2. Birds were allocated to 10 treatment groups with 12 replicates (cages) of two hens and were fed, from week 26 to 50, isocaloric and isonitrogenous experimental diets. A 5 × 2 experimental arrangement was applied, using diets with increasing level of rye (0%, 10%, 15%, 20% or 25%) with or without xylanase supplementation (200 mg/kg of feed; Ronozyme WX (CT) with minimum xylanase activity of 1, 000 FXU/g). 3. Increasing dietary level of rye did not affect daily mass of eggs, mean egg weight or feed conversion ratio ( P > 0.05). Laying rate decreased in all groups fed with rye. Egg and eggshell quality indices were unaffected by dietary rye grain ( P > 0.05); however, rye inclusion significantly decreased yolk colour on the DSM scale ( P < 0.05). In comparison with the control group, high dietary levels of rye (25%) significantly increased viscosity of small intestine content ( P < 0.05). Diet supplementation with xylanase had no significant effect on egg production indices and egg quality (except for yolk colour) but decreased the viscosity of intestinal content in laying hens fed high levels of rye ( P < 0.05). 4. The results of this experiment suggest that rye may be incorporated to a level of 25% in the diet of laying hens without any strong negative effect on egg performance, while xylanase added to high-rye grain reduced the viscosity of intestinal content; however, it did not positively affect the laying performance or egg quality.